THE EFFECT OF HEALTH EDUCATION TOWARD KNOWLEDGE OF THE ELDERLY IN MANAGEMENT RISK OF URINARY INCONTINENCE - Reni Devita (Ekonomis: Journal of Economics and Business, 2018)
One important means on the Management of human resources in a organization is the creation of job satisfaction of employees. Job satisfaction is an individual attitude, the greater aspects of the work in accordance with the wishes and goals, the higher the perceived level. Based on the above, the authors are interested in making the study titled "The Effect of Motivation and Working Conditions on Job Satisfaction In PT. Insurance Mega Pratama Jambi Branch. To obtain empirical evidence of the level of job satisfaction is influenced by two independent variables, work motivation and working conditions to the population of employees of PT. Insurance Mega Pratama Jambi Branch, it can be formulated hypotheses as follows: (1) allegedly motivated, good working conditions and job satisfaction of employees are satisfied at PT. Insurance Mega Pratama Jambi Branch; (2) allegedly contained significant influence motivation and working conditions on job satisfaction at. Insurance Mega Pratama Jambi Branch. to determine the relationship anatara independent variables with the dependent variable which is formulated as follows: Y = a + b1X1 + b2X2 + e. PT. Mega Pratama Insurance has been operating under the name PT. These Insurance Pledge Lloyd since 1959. In mid-2003, PT. Prima Executive acquire all shares of Bakrie Finance Corporation (BFC) in PT. These Insurance Lloyd Pledge. On March 8, 2004, PT. Insurance Mega Pratama officially operates with the new name. F test result showed that motivation and working conditions affect the job satisfaction. This is indicated by the value Fhitung 22.791. When compared with F table of 2.61, then the F count> F table (22.791> 2.61). T test results showed that motivation does not affect the job satisfaction while working conditions affect the job satisfaction. Based on the authors research will provide useful suggestions for the company: (1) the Head of Branch PT. Insurance Mega Pratama Jambi Branch to provide motivation and improvement of working conditions / work environment in order to improve employee job satisfaction, because based on research results and the motivation given the company a good working environment can improve employee job satisfaction, so as to improve employee performance; (2) for further research, is expected in future studies variables should develop research in order to gain a better understanding of the job satisfaction.